(untitled) (Global Journal of Human-Social Science, 2023)
The application of the rapid river assessment protocol is very important in surveying the environmental conditions of streams The present work aims to apply the protocols of Callisto et al 2001 Guimar es et al 2012 Bai o 2014 and Machado 2019 in streams in the municipality of Marip western Paran and compare the results The proposal by Callisto et al 2001 was adopted in this work as a reference in the assessment of aquatic habitats as it is a pioneering protocol in Brazil and includes a greater number of parameters The finale scores obtained at each monitoring point applying the four protocols were standardized as each proposal presents classification categories organized on different scales The normalized values showed that the protocols produced equivalent results This finding leads us to suggest that both the protocol by Guimar es et al 2012 such as Bai o 2014 and Machado 2019 all of them simpler and less extensive than Callisto et al 2001 protocol can be adopted in schools and colleges in Marip and municipalities in the region as an instrument of environmental education